A compact coplanar waveguide‐fed band‐notched four‐port flexible ultra‐wide band‐multi‐input‐multi‐output slot antenna for wireless body area network and Internet of Things applications. Issue 9 (20th June 2022) - Du, Chengzhu; Yang, Zhipeng; Zhong, Shunshi
Abstract: In this letter a novel notched multi‐input‐multi‐output (MIMO) flexible slot antenna with a C‐slot is proposed and designed for wireless body area network (WBAN) and Internet of Things (IoT) applications. The proposed antenna is comprised of four similar elements with the feed line of coplanar waveguide (CPW). Antenna is printed on flexible liquid crystal polymer (LCP) substrate with compact dimensions. The proposed UWB‐MIMO slot antenna can operate in range of 2.85–10.85 GHz with notched band from 4.9–6.425 GHz. The achieved notched band can filter the interference of WLAN (5.15–5.825 GHz), by adding an inverted orthogonal branch, great isolation is achieved, which is better than 24 dB over working bands. What's more, the parameters of diversity performance like gain, envelope correlation coefficient (ECC) and diversity gain (DG) are also analyzed. The actual measurement of bending test and the effect of human body indicates that the presented antenna is suitable for WBAN and IoT applications.